MRI of the Knee : A Guide to Evaluation and Reporting - Bolog, Nicolae V.; Andreisek, Gustav; Ulbrich, Erika J. (Springer International Publishing : Imprint: Springer, 2015)
This book is divided into chapters that cover MRI of all structures of the knee joint in the order that is usually used in practice - cruciate ligaments, collateral ligaments, menisci, cartilage, subchondral bone, patella, synovia, muscles and tendons, arteries, veins and bones. With the aid of numerous images, each chapter provides comprehensive descriptions of the anatomy, the normal MR appearance, pathological MR findings, and postoperative MRI appearance. A text box at the end of each chapter clearly describes how the MRI report should be compiled and identifies what should be included when reporting on specific lesions. The book will be an ideal guide for radiologists and will also be relevant for orthopaedic surgeons, rheumatologists, and physiotherapists.